Microwave-assisted synthesis of Z-scheme CdS/BiOBr heterojunction for improved visible-light photocatalytic degradation of organic dyes - Hu, Hanmei; Wang, Tao; Peng, Lulu; Ling, Xiaohui; He, Yunyun; Sun, Mei; Yang, Mingdi; Deng, Chonghai (Applied physics. A, Materials science & processing, 2022)
In this study, a novel CdS/BiOBr heterojunction comprising CdS quantum dots (QDs) decorated on BiOBr nanoflakes (NFs) was successfully synthesized by a facile microwave-assisted aqueous chemical synthesis technology. The crystal structure, chemical composition, and optical and electric properties were characterized by various techniques. The results demonstrated that cubic CdS QDs are planted uniformly on {001}-faced exposed tetragonal BiOBr NFs with about 30 nm thicknesses. The formation mechanism for CdS/BiOBr nanostructure was proposed. The photocatalytic performance of CdS/BiOBr heterojunction was greatly enhanced by the decomposition of organic pollutant under visible light irradiation. In particular, sample CB-3 exhibited the best photocatalytic activity for the degradation of malachite green, the fastest pseudo-first-order kinetic rate constant of which reached 0.125 min −1 , 4.4, 22.6, and 3.2 times higher than that of BiOBr, CdS and the physical mixture, respectively. The direct Z-scheme photocatalytic mechanism for CdS/BiOBr heterojunction could be attributed to the perfect band matching and the efficient charge carrier separation and transfer. Furthermore, the highly efficient photocatalytic performance for the degradation of Congo red (CR) and methyl red (MR) suggests a promising application in industrial wastewater treatment.